Ensino-aprendizagem de física: conexão e contexto em andaimes cognitivistas computacionais - Rodrigues, Gil Luna (2014)
The main goal of this study was: to organize, to implement and to discover a new methodology with theoretical-practical concept that comes to contribute for a better place in the process of teaching and learning Physics. Developed along a trajectory that connects the systemic Educational Event , Education, Learning , Educational Theories , Educational Practice and Knowledge Construction, learn is not just memorize information but it is necessary to relate them, give a new sense to them and reflect about them, where the good aspects in the cognitive structure from learners are determiners, we opted by epistemological aspects whose origin is in the Theoretical of learning meaningful (TLM) by David Ausubel. To compose a framework in a new way for a society within digital era, we choose didactics resource in the technological and communication areas of education (TCAE). During the process we used a computational tool called Objects of learning (OL), regarded as a self consistent resource by the teaching and learning process (TLP). It can be understood as a component strictly digital reused or source of virtual reproduction coherent with the phenomena of interest studied. Linking the study by the pedagogue context and putting the classroom as a stage, it was considered a new way of learning that involved the learners, the staff, an integrants of the subject Applied Physics offer by the courses of electric engineering, industrial automation, and geo-processing from The Federal Institute of Education and Science of Paraiba State (IFPB). We did the mapping and treatment of data qualitative and quantitative, the clinical method of watching, treatment almost experimental, research of intervention and diagnose aspects that made possible the acquisition, the control and analyze of the necessary elements to make possible our hypothesis of research. Ensure flexibility, connectivity and interactivity and a positive influence on the construction of the concepts of physics and application in solving these problems.